Diagnostic Capability of 3D Peripapillary Retinal Volume for Glaucoma Using Optical Coherence Tomography Customized Software. Issue 8 (August 2019) - Liu, Yingna; Jassim, Firas; Braaf, Boy; Khoueir, Ziad; Poon, Linda Yi-Chieh; Ben-David, Geulah S.; Papadogeorgou, Georgia; Tsikata, Edem; Simavli, Huseyin; Que, Christian; Lee, Ramon; Shieh, Eric; et al.
Abstract : Précis: The diagnostic capability of peripapillary retinal volume is similar to peripapillary retinal nerve fiber layer thickness for diagnosing glaucoma, but with fewer artifacts. Purpose: To compare the diagnostic capability of 3-dimensional peripapillary retinal volume (RV) versus 2-dimensional peripapillary retinal nerve fiber layer (RNFL) thickness for open-angle glaucoma. Patients and Methods: A retrospective cross-sectional analysis was conducted. A total of 180 subjects (113 open-angle glaucoma, 67 normal participants) had spectral domain optical coherence tomography volume scans and RNFL thickness measurements. Peripapillary RV values were calculated using a custom-designed program with 4 circumpapillary annuli (CA): CA1 had circle diameters of 2.5 and 3.5 mm; CA2, 3 and 4 mm; CA3, 3.5 and 4.5 mm; and CA4, 4 and 5 mm. Area under the receiver operating characteristic curves were calculated for global, quadrant, and octant regions for RV (CA1 to CA4) and RNFL thickness. Pair-wise comparisons were conducted. Artifacts rates were determined. Results: Mean age was 62.7±15.4 years, and 47.8% (86/180) were male. Among RV measurements, best diagnostic performances were for the smallest 2 annuli for inferior RV (CA1: 0.964, CA2: 0.955). Of the 4 annuli, CA1 had the highest diagnostic performance. Of specific regions, the inferior RV quadrant had the highest performance across CA1 to CA4. Peripapillary RV had similar diagnostic capability compared with RNFL thickness ( P >0.05). The artifact rate per B-scan for RV was 6.0%, which was significantly lower compared with 2-dimensional RNFL thickness in the same patient population (32.2%, P <0.0001). Conclusions: The diagnostic capability of RV is similar to RNFL thickness for perimetric open-angle glaucoma, but RV had fewer artifacts compared with RNFL thickness. Abstract : Supplemental Digital Content is available in the text.